2003
DOI: 10.1016/s0886-3350(02)01619-x
|View full text |Cite
|
Sign up to set email alerts
|

Scheimpflug photography study of ophthalmic viscosurgical devices during simulated cataract surgery

Abstract: The capacity of Healon5 to maintain the ACD during cataract surgery, ie, neutralizing the vitreous pressure and stabilizing the anterior segment of the eye, was significantly higher than that of the other OVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Healon5 acts as a very viscous, cohesive agent at low flow rates and as a pseudodispersive agent at higher flow rates. The capacity of Healon5 to maintain the anterior chamber depth during simulated cataract surgery in porcine cadaver eyes was significantly higher than that of the other OVDs (Holmén & Lundgren 2002). However, at flow rates of approximately 25 cm 3 /min or over, this agent would tend to flow out of the eye.…”
Section: Discussionmentioning
confidence: 89%
“…Healon5 acts as a very viscous, cohesive agent at low flow rates and as a pseudodispersive agent at higher flow rates. The capacity of Healon5 to maintain the anterior chamber depth during simulated cataract surgery in porcine cadaver eyes was significantly higher than that of the other OVDs (Holmén & Lundgren 2002). However, at flow rates of approximately 25 cm 3 /min or over, this agent would tend to flow out of the eye.…”
Section: Discussionmentioning
confidence: 89%
“…While this method is very useful, it is difficult to observe the cross section between the corneal endothelium and the phaco tip in detail. Holmén and Lundgren have reported that the use of a surgical microscope for the anterior segment analysis system (EAS-1000, Nidek Co., Ltd.) enabled comparison of the anterior chamber depth maintenance and retention capacities of the commercially available OVDs, within a porcine cadaver eye model during simulated phacoemulsification [ 15 ]. Although results obtained by this method allow better understanding of the retention of OVDs in the anterior chamber with partial observation, it remains impossible to analyze fluid dynamics and retention of OVDs in the anterior chamber during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%